Early Steroid-Induced Osteonecrosis of Rabbit Femoral Head and Panax notoginseng Saponins: Mechanism and Protective Effects. (16th March 2015) - Qiang, Hui; Liu, Huitong; Ling, Ming; Wang, Kunzheng; Zhang, Chen
Abstract : Background. This study was aimed at investigating the pathogenesis of oxidative stress in steroid-induced avascular necrosis of the femoral head (SANFH) and at exploring the mechanism and protective effects of Panax notoginseng saponins (PNS) on early SANFH. Methods. 80 adult New Zealand rabbits were randomly divided into control group, model group, and PNS group. In model group, equine serum was injected into auricular vein; then methylprednisolone was injected into gluteus. In PNS group, PNS was applied for 14 consecutive days before methylprednisolone management. At different time points, serum and femoral heads were prepared for T-AOC, SOD, GSH-PX, ·OH, and MDA determination. Two weeks after steroid management, all femoral heads were assessed with MRI and HE staining. Results. Typical early osteonecrosis symptoms were observed in model group. Our results showed that PNS could significantly ameliorate the decrease of T-AOC level, improve SOD and GSH-PX activity, suppress ·OH ability, and augment MDA level. Besides, PNS improved MRI and pathological changes of the femoral head, markedly reducing the incidence of osteonecrosis. Conclusion. Based on our research, we found oxidative stress played a positive role in the occurrence of SANFH where reactive oxygen species was the direct cause. PNS could protect rabbits against early steroid-induced osteonecrosis of femoral head by its antioxidative effect.